Digital Entrepreneurship Among Students: Driving Factors, Challenges, and Career Orientation - Ariani, Dewi; Hanafi, Syadeli; Atikah, Cucu (Pinisi Journal of Entrepreneurship Review, 2026)
This study explores the phenomenon of digital entrepreneurship among college students in response to rapid technological transformation and evolving career orientations. Using a qualitative phenomenological approach, this study examines students' lived experiences in starting and managing digital-based businesses, focusing on their driving factors, challenges, and future career orientations. Data were collected through in-depth interviews with seven students actively involved in digital businesses, then analyzed using the Colaizzi method supported by NVivo 14 software. The findings revealed three interrelated themes: the driving factors for students to become digital entrepreneurs are stimulated by the role of parents, the desire to earn money or income, developing self-skills, challenges faced generally difficult in time management, lack of consistency, difficulty finding customers, limited capital, busy studies, and career orientation as a digital entrepreneur is still lacking because students only consider digital entrepreneurship as an alternative career choice, where the main career choice is working in a company or agency. This study concludes that digital entrepreneurship is not only an economic activity but also a process of identity formation and individual adaptation to a technology-driven economy that needs to be improved. This highlights the importance of developing a sustainable digital entrepreneurship ecosystem in higher education through incubators, mentoring, and experiential learning to foster innovation, independence, and readiness for the digital economy.